Bottom-Up Self-Organization in Supramolecular Soft Matter Principles and Prototypical Examples of Recent Advances - Müller, Stefan C.; Parisi, Jürgen (Springer Series in Materials Science, 2015)
This book presents the general concepts of self-organized spatio-temporal ordering processes. These concepts are demonstrated via prototypical examples of recent advances in materials science. Particular emphasis is on nanoscale soft matter in physics, chemistry, biology and biomedicine. The questions addressed embrace a broad spectrum of complex nonlinear phenomena, ranging from self-assembling near the thermodynamical equilibrium to dissipative structure formation far from equilibrium. Their mutual interplay gives rise to increasing degrees of hierarchical order. Analogues are pointed out, differences characterized and efforts are made to reveal common features in the mechanistic description of those phenomena.  .